Electrically evoked compound action potentials are different depending on the site of cochlear stimulation. (1st November 2016) - van de Heyning, Paul; Arauz, Santiago L.; Atlas, Marcus; Baumgartner, Wolf-Dieter; Caversaccio, Marco; Chester-Browne, Ronel; Estienne, Patricia; Gavilan, Javier; Godey, Benoit; Gstöttner, Wolfgang; Han, Demin; Hagen, Rudolph; et al.
Abstract : One of the many parameters that can affect cochlear implant (CI) users' performance is the site of presentation of electrical stimulation, from the CI, to the auditory nerve. Evoked compound action potential (ECAP) measurements are commonly used to verify nerve function by stimulating one electrode contact in the cochlea and recording the resulting action potentials on the other contacts of the electrode array. The present study aimed to determine if the ECAP amplitude differs between the apical, middle, and basal region of the cochlea, if double peak potentials were more likely in the apex than the basal region of the cochlea, and if there were differences in the ECAP threshold and recovery function across the cochlea. ECAP measurements were performed in the apical, middle, and basal region of the cochlea at fixed sites of stimulation with varying recording electrodes. One hundred and forty one adult subjects with severe to profound sensorineural hearing loss fitted with a Standard or FLEX SOFT electrode were included in this study. ECAP responses were captured using MAESTRO System Software (MED-EL). The ECAP amplitude, threshold, and slope were determined using amplitude growth sequences. The 50% recovery rate was assessed using independent single sequences that have two stimulation pulses (a masker and a probe pulse) separated by a variable inter-pulse interval. For all recordings, ECAP peaks were annotated semi-automatically. ECAP amplitudes were greater upon stimulation of the apical region compared to the basal region of the cochlea. ECAP slopes were steeper in the apical region compared to the basal region of the cochlea and ECAP thresholds were lower in the middle region compared to the basal region of the cochlea. The incidence of double peaks was greater upon stimulation of the apical region compared to the basal region of the cochlea. This data indicates that the site and intensity of cochlear stimulation affect ECAP properties.